The Indo-Pacific Context : Maritime Security Challenges And Diplomacy Of Asean Countries - Endyka Triono Dachi; Moch Yurianto; Purwanto (CV. AFDIFAL MAJU BERKAH, 2023)
The Indo-Pacific region is considered strategic considering that there are intersections in international trade routes in it. Meanwhile, the strategic value as a geopolitical center is emphasized by the presence of strong countries such as the United States, China, India, Australia, Japan, as well as ASEAN countries. Based of the problem that has been described, the objective of this article is to examine the strategies and diplomatic efforts of ASEAN countries in dealing with maritime security threats in the Indo-Pacific Region. The study used qualitative methods with descriptive research design. This research through the Zoom Meeting application by inviting representative speakers from Universitas Pertahanan Malaysia. The activity will be held on 28 June-2 July 2021. Theoritical framework in this article using maritime security concept, maritime diplomacy concept, and Indo-Pacific Concept. The conclusion is the feud between China and the United States in the Indo-Pacific region, especially the South China Sea has the potential to disrupt regional stability and security. Maritime security related to undisturbed shipping traffic and communications is an effort that the United States is guarding. China's presence in the South China Sea area threatens the interests of the United States regarding sea traffic which will have an impact on the global economy and its country if no action is taken. Countries in Southeast Asia see this problem as something that must be resolved. The presence of AOIP is expected to be able to help resolve existing problems regarding actions that are carried out individually by ASEAN member countries.